2(y+7)=-3(3y-4)+7y

Simple and best practice solution for 2(y+7)=-3(3y-4)+7y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(y+7)=-3(3y-4)+7y equation:



2(y+7)=-3(3y-4)+7y
We move all terms to the left:
2(y+7)-(-3(3y-4)+7y)=0
We multiply parentheses
2y-(-3(3y-4)+7y)+14=0
We calculate terms in parentheses: -(-3(3y-4)+7y), so:
-3(3y-4)+7y
We add all the numbers together, and all the variables
7y-3(3y-4)
We multiply parentheses
7y-9y+12
We add all the numbers together, and all the variables
-2y+12
Back to the equation:
-(-2y+12)
We get rid of parentheses
2y+2y-12+14=0
We add all the numbers together, and all the variables
4y+2=0
We move all terms containing y to the left, all other terms to the right
4y=-2
y=-2/4
y=-1/2

See similar equations:

| 2(y+7)=-3(3y-4 | | (2x-9)+x=180 | | 5x+-7=3x+-3 | | (11-5x)/x=0 | | 2x+5=10-3x=10-3x | | 1÷3g=6 | | (3d-12)-(2d+3)=d-15 | | 10x+2=5(2x+1)-3 | | 3/4x=-9= | | V+7=-3+2v | | 7+8y+7=10y+6 | | -8t+7=9-7t | | (-2+3n)=8 | | 3(×+3)+4x=15-2×3 | | -89+z=-38,z= | | -7.92+5.4w=4.4w+7.04+2.7w | | -31.5=-6b,b= | | 4–9g=-23,g= | | 4n=-23 | | -9+6h=9+8h | | –38=2n | | 36+3w=-36,w= | | -6x–18=18,x | | 550t=150(t+4) | | -6x–18=18,x= | | 2x-17=10x | | 5d+20=-30,d= | | 4x+10=2x+34 | | 13+2a=13 | | 3x+23=-80 | | (x-4)/4-(x+7)/6=(5x-4)/9 | | 9x-40=7x-37+3x+23=180 |

Equations solver categories